2005
DOI: 10.1351/pac200577091497
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of dancing with vanadium

Abstract: The advances in vanadium chemistry over the past 15 years are discussed in the areas of solution chemistry, coordination chemistry, and bioinorganic chemistry and will be presented using the perspectives of "What exists in solution?", "What is its structure?", "How does it react?", and "What are its biological effects?". Current and future challenges will be described briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 118 publications
(199 reference statements)
1
80
0
1
Order By: Relevance
“…In particular, their potential insulin mimetic capacity has been extensively investigated [10][11][12][13][14][15][16]. It has been shown that VCs can be used to mitigate insufficient insulin response in DM thus presenting insulin-mimetic properties in vitro and [17][18][19][20] in vivo [21][22][23][24], and two of them were tested in clinical trials [25].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, their potential insulin mimetic capacity has been extensively investigated [10][11][12][13][14][15][16]. It has been shown that VCs can be used to mitigate insufficient insulin response in DM thus presenting insulin-mimetic properties in vitro and [17][18][19][20] in vivo [21][22][23][24], and two of them were tested in clinical trials [25].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, despite a number of studies pointing towards the biological importance of vanadate and its polyoxo forms, the molecular basis of this activity remains largely unexplored, as these studies are often hindered by the complex solution chemistry of vanadate and the existence of equilibria with different polyoxoanions at physiological pH. 7,8 While it has been mainly assumed that the mode of action of oxovanadates mostly depends on their structural features such as the charge and the size of the species, 9 their reactivity towards biologically relevant substrates has been very scarcely explored. Recent studies on the biological relevance of polyoxometalates revealed the unprecedented hydrolytic activity of oxovanadates towards several important classes of compounds such as phosphodiesters, monophosphoesters 10,11 and carboxylic esters.…”
Section: Introductionmentioning
confidence: 99%
“…6,15,16 However, various approaches to address this problem have provided some further insight as to the biological activity of these compounds. [5][6][7]16,20 Information on how effectively specific compounds inhibit isolated enzymes is important for consideration of their mode of actions in cells and animals. 6 A range of studies of a few vanadium compounds on isolated enzyme systems have been reported where the species exerting the effects can be more rigorously tracked.…”
Section: Introductionmentioning
confidence: 99%